2003
DOI: 10.1099/jmm.0.04901-0
|View full text |Cite
|
Sign up to set email alerts
|

Lack of flagella disadvantages Salmonella enterica serovar Enteritidis during the early stages of infection in the rat

Abstract: The roles of flagella and five fimbriae (SEF14, SEF17, SEF21, pef, lpf) in the early stages (up to 3 days) of Salmonella enterica serovar Enteritidis (S. Enteritidis) infection have been investigated in the rat. Wild-type strains LA5 and S1400 (fim+/fla+) and insertionally inactivated mutants unable to express the five fimbriae (fim2/fla+), flagella (fim+/fla2) or fimbriae and flagella (fim2/fla2) were used. All wild-type and mutant strains were able to colonize the gut and spread to the mesenteric lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 46 publications
2
35
0
2
Order By: Relevance
“…Bacterial flagellin is a virulence factor of S. enterica. Strains of Salmonella deficient in flagellin can exhibit defects in colonization and tissue invasion, as well as invasion of macrophages and epithelial cells in vitro [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial flagellin is a virulence factor of S. enterica. Strains of Salmonella deficient in flagellin can exhibit defects in colonization and tissue invasion, as well as invasion of macrophages and epithelial cells in vitro [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for this phenomenon is still unknown. Many studies have shown the importance of flagella for virulence of S. enterica serovars (87,182,188,197), although the specific aspect of flagellar function that contributes to virulence remains unclear.…”
Section: Fliamentioning
confidence: 99%
“…Salmonella lacking flagellin expression were initially reported to have reduced virulence (43,44), but this finding was later refuted (45,46). The most recent data indicate that nonflagellated bacteria have reduced virulence in cell culture experiments, but are virulent, or only have slightly reduced virulence in vivo (47,48). However, the effect of Salmonella flagellin overexpression has not been examined.…”
mentioning
confidence: 99%